Model-based planning for post-conflict reconstruction: The case of Yemen - Breisinger, Clemens; Engelke, Wilfried; Mukashov, Askar; Wiebelt, Manfred (International Food Policy Research Institute, 2020)
Evidence-based planning for post-conflict reconstruction is often constrained by missing data and the shortcomings of conventional analytical methods. To overcome these constraints, we use economy-wide modeling methods to model the impact of war and reconstruction possibilities for the economy of Yemen. We first calibrate the model to pre-conflict data (2014) and validate it by replicating the most recent available dynamic needs assessments for Yemen that were elaborated by the World Bank. We then report model scenario results for unobserved development indicators, such as estimates for sector-level growth, employment, and poverty. For the post-conflict period, we use the assumptions of a recent dynamic needs assessment and assume gradual reconstruction of the war-induced damages by the target year 2024. Then we focus on uncertain institutional factors and investigate their importance for the country’s socio-economic development. Finally, we assess the potential structural characteristics of Yemen’s economy in the year 2024 and analyze potential risks and trade-offs associated with government’s institutional performance and the implications these have for the pace of post-conflict reconstruction.